Rabbit hole. Season one [videorecording (DVD)] - Requa, John; Ficarra, Glenn; Khosla, Siddhartha, 1977- (CBS Studios, 2023)
Nothing is what it seems when John Weir, a master of deception in the world of corporate espionage, is framed for murder by powerful forces with the ability to influence and control populations. The series stars Emmy Award Winner, Kiefer Sutherland as private espionage operative John Weir, who finds himself in the midst of a battle over the preservation of democracy in a world at odds with misinformation, behavioral manipulation, the surveillance state, and the interests that control these extraordinary powers.